1997
DOI: 10.1103/physrevlett.79.2542
|View full text |Cite
|
Sign up to set email alerts
|

Disorder-Induced Transition to Entangled Vortex Solid in Nd-Ce-Cu-O Crystal

Abstract: Local magnetic measurements in a highly anisotropic Nd-Ce-Cu-O crystal reveal a sharp onset of an anomalous magnetization peak at a temperature-dependent field B on . The same field marks a change in the field profiles across the sample, from profiles dominated by geometrical barriers below B on to Bean-like profiles above it. The temperature dependence of B on and the flux distribution above and below B on imply a disorder-induced transition at B on from a relatively ordered vortex lattice to a highly disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
134
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 25 publications
15
134
3
Order By: Relevance
“…1 of Ref. [123] illustrates a very successful phenomenological fit to the experimental data on the BrG-MG phase boundary in NCCO. This phase boundary was assigned to the locus of onset points of the fishtail anomaly.…”
Section: Comparison To Experimental Resultsmentioning
confidence: 99%
“…1 of Ref. [123] illustrates a very successful phenomenological fit to the experimental data on the BrG-MG phase boundary in NCCO. This phase boundary was assigned to the locus of onset points of the fishtail anomaly.…”
Section: Comparison To Experimental Resultsmentioning
confidence: 99%
“…As a result the magnetic curves are more regular. The overall behavior resembles the SMP observed usually in high-T c superconductors [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. For this reason we "loosely" refer to these characteristic fields as H′′ smp ′′ .…”
Section: Tmis and The "Smp" In Magnetic Measurementsmentioning
confidence: 99%
“…Recent magnetic studies in Nb films [1,2,3] reported the existence of a structure that reminisces of the second magnetization peak (SMP) which is usually observed in high-T c superconductors [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19]. These studies concluded that for the case of Nb films the "SMP" is probably motivated by thermomagnetic instabilities (TMIs) that occur in the low-temperature regime, far below the uppercritical field [1,2,3].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increase of random pinning or magnetic field a transition to strongly disordered entangled vortex phase (glass phase) is predicted [5,6]. A sharp increase in magnetization below the fish-tail peak position H p was observed in N d 1.85 Ce 0.15 CuO 4−d [7] and non twinned YBa 2 Cu 3 O 7−δ [8] single crystals.Magnetic measurements showed that in optimally doped YBa 2 Cu 3 O 7−δ crystals no fishtail behavior is observed both in detwinned [9] and twinned [10] samples, while decrease of the oxygen content always induced non monotonous J m (H)-curves. Two distinctive peculiarities in the magnetization curves of oxygen deficient [10] and electron irradiated [11] crystals were observed: (1) the peaks H on and H p shift toward lower magnetic fields with increasing defect concentration, and (2) in magnetic fields H < H p the current J m increases, while in magnetic fields H > H p the current J m decreases with increasing defect concentration.…”
mentioning
confidence: 99%
“…However, with the increase of random pinning or magnetic field a transition to strongly disordered entangled vortex phase (glass phase) is predicted [5,6]. A sharp increase in magnetization below the fish-tail peak position H p was observed in N d 1.85 Ce 0.15 CuO 4−d [7] and non twinned YBa 2 Cu 3 O 7−δ [8] single crystals.…”
mentioning
confidence: 99%